Designing model for improving relationship of wives with men with erectile dysfunction - Ozgoli, giti; Ziaei, saeeideh; Ahmadi, fazllolah; Azar, mahyar (Advances in Nursing & Midwifery, 2015)
Abstract Background and Aim: Studies have shown erectile dysfunction is a common problem in men which has negative impact on both man and his partner. This dysfunction causes sexual and marital relationship difficulties. Efforts are not effective until relationship has not been improved. Thus the purpose of this study is to design a model for improving relationship of wives with men with erectile dysfunction. Materials and Methods: This is a qualitative study; data collecting method was unstructured interview with 16 female partners of men with erectile dysfunction. Field notes were also used as data. Constant comparison analysis was done simultaneously using Strauss and Corbin method. Sexuality in female partners of men with erectile dysfunction was explained using grounded theory. The model which improves the relationship between wives and men with erectile dysfunction was composed using the findings of grounded theory and literature review based on the Walker and Avant theory synthesis method. Findings: results of this grounded theory indicted that loss of intimacy was the main concern of female partners of men with erectile dysfunction. And main strategy in facing with sexuality was preserving the family unity. In this model, unlike the existing models, the starting point for sexual dysfunction treatment is the female partner. This model designed through three phases: first phase was aimed to identify the status of marital relationship, second phase was aimed to empower women participation of spouses, and third phase was aimed to perform holistic interventions to stabilize desirable marital relationship. Conclusion: Using this model, in sexual problem condition, at first woman, then couple will be empowered. Thus the overall marital relationship will not be damaged or the intensity of damage will be reduced. Key word: Erectile dysfunction, Sexual problem, Sexual relationship, Marital relationship, Mod